1998
DOI: 10.1101/gad.12.21.3357
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of coactivator LXXLL motif specificity in nuclear receptor transcriptional activation

Abstract: Ligand-dependent activation of gene transcription by nuclear receptors is dependent on the recruitment of coactivators, including a family of related NCoA/SRC factors, via a region containing three helical domains sharing an LXXLL core consensus sequence, referred to as LXDs. In this manuscript, we report receptor-specific differential utilization of LXXLL-containing motifs of the NCoA-1/SRC-1 coactivator. Whereas a single LXD is sufficient for activation by the estrogen receptor, different combinations of two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

26
474
4
10

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 568 publications
(514 citation statements)
references
References 56 publications
26
474
4
10
Order By: Relevance
“…Similarly, the only agonist-derived peptide identified in our screen that was unable to bind VDR also lacked the consensus sequence. In summary, our results are consistent with previous studies that stress the importance of residues N-terminal to the LxxLL motif to overall receptor selectivity [9,12,13], which is in contrast to a recent study that suggested receptor recognition is dictated by residues C-terminal to the motif [11].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Similarly, the only agonist-derived peptide identified in our screen that was unable to bind VDR also lacked the consensus sequence. In summary, our results are consistent with previous studies that stress the importance of residues N-terminal to the LxxLL motif to overall receptor selectivity [9,12,13], which is in contrast to a recent study that suggested receptor recognition is dictated by residues C-terminal to the motif [11].…”
Section: Discussionsupporting
confidence: 93%
“…The enhancement of transcriptional activity is dependent upon the integrity of the motif along with key residues in helix 12 (AF-2) of the nuclear receptor ligandbinding domain [9,10]. In addition, studies have shown receptor selectivity for coactivators by detailing the importance of sequences N and C-terminal to the LxxLL motif [9,[11][12][13]. Furthermore, there is evidence for ligand-specific recruitment of coactivators.…”
Section: Introductionmentioning
confidence: 99%
“…In our study we detected CIZ1 -RD and CIZ1 -AD amplicons in regions unrelated to exon 8 in order to avoid this highly variable region of CIZ1 . CIZ1 binding to (PR) has not been previously studied; though it has been shown that, in the context of NCoA-1/SRC-1, PR also requires two LXXLL domains [36]. Thus, while we could find no functional response to estrogen in MCF-7 cells, the presence of these domains and the correlation with breast tumor receptor status supports a relationship in vivo .…”
Section: Discussionsupporting
confidence: 51%
“…ARNT is the central heterodimerization partner of several transcription factors, including those containing the aryl-hydrocarbon (dioxin) receptor (AhR) and the hypoxia-inducible factor 1alpha (HIF-1alpha). A report that the AhR/ARNT heterodimer directly associates with oestrogen receptor-a and -b is interesting in light of our identification of an LXXLL motif or nuclear receptor box in the N-terminus of the PASD1 protein that might mediate similar interactions (McInerney et al, 1998). While no studies have directly implicated AhR/ARNT in lymphomagenesis, it has been linked to leukaemogenesis (Salomon-Nguyen et al, 2000;Hayashibara et al, 2003).…”
Section: Discussionmentioning
confidence: 99%